Phytochemical Analysis, Antioxidant and Pharmacological Evaluation of Antidiabetic Activity of Methanolic Extract of Geranium wallichianum D. Don ex Sweet in Alloxan-Induced Diabetic Rats - Fatima Afzal; Abdul Aleem; Javed Iqbal; Fahad Asim; Irfan Anjum; Muhammad Naveed Mushtaq (Journal of Pharmaceutical Innovation, 2026)

Parametric study on the mechanical response of a plate-monopile hybrid foundation in sand under cyclic loading - Yukun Ma; Chuanjie Xu; Subhamoy Bhattacharya; Haoyuan Liu; Muhammad Aleem; Liang Cui (Soil Dynamics and Earthquake Engineering, 2026)

Integrated sedimentological and petrographic constraints on early Himalayan foreland basin evolution, Sulaiman ranges, Pakistan - Muhammad Jehangir Khan; Shahid Ghazi; Xiaodong Yang; Syed Ahsan Hussain Gardezi; Mubashir Mehmood; Muhammad Aleem Zahid; Umair Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Assessment of growth and physiological effects of dietary Arthrospira platensis in broiler chickens - Zain Ul Abideen; Muhammad Zeshan Haider; Muhammad Kashif Zaman; Muhammad Farooq; Amin F. Majdalawieh; Imad A. Abu-Yousef; Tahira Ruby; Aleem Ahmed Khan (Livestock Science, 2026)

Cyclic behaviour of plate-monopile and bucket-monopile hybrid foundation in sand - Yukun Ma; Sanchari Mondal; Ge Cui; Muhammad Aleem; Subhamoy Bhattacharya; Liang Cui (Computers and Geotechnics, 2026)

Mechanical responses of plate-monopile hybrid foundation under cyclic load with different patterns - Yukun Ma; Chuanjie Xu; Sayan Bhattacharyya; Subhamoy Bhattacharya; Muhammad Aleem; Liang Cui (Ocean Engineering, 2026)

Designing glass materials for renewable-energy production through building integrated photovoltaics (BIPV) −A computational approach - Aqsa Aleem; Uzma Habib; Waqas Salman; Muhammad Tariq Saeed (Energy and Buildings, 2026)

Characterization and fungicidal sensitivity of Phytophthora species causing citrus gummosis in Pakistan - Hadeed Ahmad; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Muhammad Hamza Shahid; Muhammad Usman Ali; Owais Iqbal; Muhammad Luqman Aleem; Qurban Ali; Nasir Ahmed Rajput (Physiological and Molecular Plant Pathology, 2026)

Predictive modelling of radon variations in time series using wavelets, multiple linear regression and ARIMA - Nadeem Bashir; Awais Rasheed; Muhammad Osama; Adil Aslam Mir; Muhammad Rafique; Saeed Ur Rahman; Dimitrios Nikolopoulos; Muhammad Abdul Basit; Aftab Alam; Aleem Dad Khan Tareen; Kimberlee Jane Kearfott (Isotopes in Environmental and Health Studies, 2025)

Thermodynamic evaluation of advanced adsorbents for thermally-driven atmospheric water harvesting system in diverse climatic conditions - Muhammad Sultan; Aïssa Rezzoug; Muhammad Aleem (International Journal of Refrigeration, 2025)

Numerical investigations on RC beam-column structures under collapse phenomenon—a simplified finite element approach - Aleem Ullah; Abdul Qadir Bhatti; Attiq Ur Rahman Dogar; Girum Urgessa; Muhammad Usman (Innovative Infrastructure Solutions, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Identification of soil damping for stiff piles based on experiments: Soil damping curves from physical model tests - Sachin Jindal; Ulvi Rahmanli; Muhammad Aleem; Liang Cui; Subhamoy Bhattacharya (Ocean Engineering, 2024)

Geotechnical challenges in monopile foundations and performance assessment of current design methodologies - Sachin Jindal; Ulvi Rahmanli; Muhammad Aleem; Liang Cui; Subhamoy Bhattacharya (Ocean Engineering, 2024)

Optimization of inclusion level of lipid in larval diet of Labeo rohita (Hamilton, 1822) - Javeria Shamas; Amina Zuberi; Muhammad Aleem Khan; Shanza Gul; Mashooq Ali; Muhammad Kamran (Fish Physiology and Biochemistry, 2024)

Identification of soil damping for stiff piles based on experiments: Methodology and results - Sachin Jindal; Ulvi Rahmanli; Muhammad Aleem; Liang Cui; Saleh Jalbi; Subhamoy Bhattacharya (Ocean Engineering, 2024)

Corrigendum to “Automated anomalous behaviour detection in soil radon gas prior to earthquakes using computational intelligence techniques” [J. Environ. Radioact. 203 (2019) 48-54] - Aleem Dad Khan Tareen; Asim Khawaja; Kimberlee Jane Kearfott; Muhammad Rafique; Malik Sajjad Ahmed Nadeem; Talat Iqbal; Saeed Ur Rahman (Journal of Environmental Radioactivity, 2023)

Unrivalled insight into potential biopharmaceutical application of Saussurea albescens (DC.) Sch.Bip.: Chemical profiling, antioxidant and enzyme inhibition activities and in silico studies - Muhammad Imran Tousif; Muhammad Saleem; Saba Tauseef; Mamona Nazir; Tahira Ruby; Reaz Uddin; Sharon Elaine D'souza; Muhammad Aleem Ashraf; Ghulam Mustafa Kamal; Jallat Khan; Gokhan Zengin (Biocatalysis and Agricultural Biotechnology, 2023)

Soil–Structure Interactions for the Stability of Offshore Wind Foundations under Varying Weather Conditions - Liang Cui; Muhammad Aleem; Shivashankar; Subhamoy Bhattacharya (Journal of Marine Science and Engineering, 2023)
Fixed-bottom foundations of offshore structures, mainly monopiles, are subject to extreme events and other critical cyclic nature loads. Since offshore wind turbine structures are slender, the manufacturers of offshore wind turbines give a range of frequencies for safe operation during a structure’s life cycle. Highly reliable measurements and accurate determination of shear moduli and damping ratios are crucial to ensure the stability of these structures, for example, to avoid the resonance of the structures. Because foundation–soil properties change over a period of time due to various environmental factors, this should be taken into consideration for designs. In the current investigation, behaviours of dry sand under dynamic loads were explored. Cyclic loads of strain amplitudes of 0.05%, 0.1%, 0.25% and 0.5% were carried out in a cyclic simple shear apparatus to explore the evolution trend of the stiffness and damping ratio of the soil. Attempts were made to simulate varying weather conditions by conducting cyclic tests with different strain amplitudes representing normal weather conditions and extreme weather conditions. It was found that soil dynamic properties vary remarkably at first and then tend to stabilise under cyclic loading with the same strain amplitude. However, with varying strain amplitude, property variations continue further. From numerical analyses using the discrete element method, it was found that this is due to the disturbance of soil, causing further particle rearrangements and soil compactions, following a sudden change of strain amplitude, which leads to further property variations.

A novel approach for power enhancement of vertical mounted bifacial photovoltaic system using reflecting mirrors - Muhammad Aleem Zahid; Hasnain Yousuf; Youngkuk Kim; Junsin Yi; Suresh Kumar Dhungel (Journal of Cleaner Production, 2023)

Anticonvulsant activity of methanolic extract of Withania cogulans in mice - Zenat Fatima Khattak; Bushra Ansari; Muhammad Jamal; Abdul Aleem Awan; Muhammad Azhar Sherkheli; Rizwan ul Haq (Metabolic Brain Disease, 2021)

Correction to: First report of Alternaria alternata causing post‑harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

First report of Alternaria alternata causing post-harvest brown spot of Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Naveed Aslam; Tanvir Ahmad; Ambreen Maqsood; Muhammad Shafique (Journal of Plant Pathology, 2021)

Outer Membrane Protein‐Coated Nanoparticles as Antibacterial Vaccine Candidates - Majid Anwar; Faqir Muhammad; Bushra Akhtar; Muhammad Irfan Anwar; Ahmad Raza; Abdul Aleem (International Journal of Peptide Research and Therapeutics, 2021)

Physical Modelling of Offshore Wind Turbine Foundations for TRL (Technology Readiness Level) Studies - Subhamoy Bhattacharya; Domenico Lombardi; Sadra Amani; Muhammad Aleem; Ganga Prakhya; Sondipon Adhikari; Abdullahi Aliyu; Nicholas Alexander; Ying Wang; Liang Cui; Saleh Jalbi; Vikram Pakrashi; et al. (Journal of Marine Science and Engineering, 2021)
Offshore wind turbines are a complex, dynamically sensitive structure due to their irregular mass and stiffness distribution, and complexity of the loading conditions they need to withstand. There are other challenges in particular locations such as typhoons, hurricanes, earthquakes, sea-bed currents, and tsunami. Because offshore wind turbines have stringent Serviceability Limit State (SLS) requirements and need to be installed in variable and often complex ground conditions, their foundation design is challenging. Foundation design must be robust due to the enormous cost of retrofitting in a challenging environment should any problem occur during the design lifetime. Traditionally, engineers use conventional types of foundation systems, such as shallow gravity-based foundations (GBF), suction caissons, or slender piles or monopiles, based on prior experience with designing such foundations for the oil and gas industry. For offshore wind turbines, however, new types of foundations are being considered for which neither prior experience nor guidelines exist. One of the major challenges is to develop a method to de-risk the life cycle of offshore wind turbines in diverse metocean and geological conditions. The paper, therefore, has the following aims: (a) provide an overview of the complexities and the common SLS performance requirements for offshore wind turbine; (b) discuss the use of physical modelling for verification and validation of innovative design concepts, taking into account all possible angles to de-risk the project; and (c) provide examples of applications in scaled model tests.

Demographic and morphometric features of pink bollworm, Pectinophora gossypiella (Saunder) (Lepidoptera: Gelechiidae) on four host plants - Muhammad Naeem Mushtaq; Muhammad Arshad; Shahid Majeed; Sajid Aleem Khan (International Journal of Tropical Insect Science, 2021)

Green remediation of saline–sodic Pb-factored soil by growing salt-tolerant rice cultivar along with soil applied inorganic amendments - Muhammad Mazhar Iqbal; Tayyaba Naz; Mazhar Iqbal Zafar; Muhammad Imtiaz; Omer Farooq; Atique ur Rehman; Shafaqat Ali; Muhammad Rizwan; Sabir Hussain; Wasim Javed; Ghulam Murtaza; Muhammad Afzal; et al. (Paddy and Water Environment, 2020)

First report of post-harvest Fusarium rot caused by Fusarium oxysporum on Citrus reticulata Blanco cv. ‘Kinnow’ in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Muhammad Fahim Abbas; Aqleem Abbas; Rana Binyamin (Journal of Plant Pathology, 2020)

Effect of Buried Straw Layer Coupled with Fertigation on Florescence and Yield Parameters of Chinese Cabbage Under Greenhouse Environment - Ghulam Rasool; Xiangping Guo; Zhenchang Wang; Muhammad Hassan; Muhammad Aleem; Qaiser Javed; Sheng Chen (Journal of Soil Science and Plant Nutrition, 2020)

Coagulation- and Adsorption-Based Environmental Impact Assessment and Textile Effluent Treatment - Muhammad Aleem; Jiashun Cao; Chao Li; Haroon Rashid; Yang Wu; Muhammad Imran Nawaz; Muhammad Abbas; Muhammad Waqar Akram (Water, Air, & Soil Pollution, 2020)

First report of post-harvest rot of Citrus reticulata cv. ‘Kinnow’ caused by Rhizopus arrhizus in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Aman Ullah Malik; Mark Lawrence Gleason; Binyamin Rana; Muhammad Amjad Ali (Journal of Plant Pathology, 2020)

First report of Alternaria brown spot of Citrus reticulata cv. ‘Kinnow’ caused by Alternaria arborescens in Pakistan - Anam Moosa; Ayaz Farzand; Muhammad Fahim Abbas; Shahbaz Talib Sahi; Sajid Aleem Khan; Mark Lawrence Gleason (Journal of Plant Pathology, 2020)

Effects of silicon nanoparticles on growth and physiology of wheat in cadmium contaminated soil under different soil moisture levels - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Adrees; Muhammad Farooq Qayyum; Sofia Khalid; Muhammad Zia ur Rehman; Muhammad Aleem Sarwar (Environmental Science and Pollution Research, 2020)

Pore size distribution and reservoir characterization: evaluation for the Eocene beach-bar sequence, Dongying Depression, China - Muhammad Aleem Zahid; Dong Chunmei; Alexandra N. Golab; Chengyan Lin; Xianguo Zhang; Xinmin Ge; Wu Songtao; Muhammad Jawad Munawar; Cunfei Ma; Lydia Knuefing (Arabian Journal of Geosciences, 2019)

Salinity stress in cotton: effects, mechanism of tolerance and its management strategies - Iram Sharif; Saba Aleem; Jehanzeb Farooq; Muhammad Rizwan; Abia Younas; Ghulam Sarwar; Shahid Munir Chohan (Physiology and Molecular Biology of Plants, 2019)

Long-term changes of a waterbird community over 26 years at a Pakistani Ramsar Site - Imran Khaliq; Muhammad Irshad Arshad; Anwar Hussain Gill; Abdul Aleem Chaudhry; Muhammad Anwer Maan; Muhammad Anwar Iqbal; Muhamad Akbar; Diana E. Bowler (Wetlands Ecology and Management, 2019)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

Therapeutic potential of dairy bioactive peptides: A contemporary perspective - Saira Sultan; Nuzhat Huma; Masood Sadiq Butt; Muhammad Aleem; Munawar Abbas (Critical Reviews in Food Science and Nutrition, 2018)

In silico transcriptional regulation and functional analysis of dengue shock syndrome associated SNPs in PLCE1 and MICB genes - Malik Mumtaz Taqi; Durdana Waseem; Humaira Ismatullah; Syed Aleem Haider; Muhammad Faisal (Functional & Integrative Genomics, 2016)

Human aging in the post-GWAS era: further insights reveal potential regulatory variants - Syed Aleem Haider; Muhammad Faisal (Biogerontology, 2015)

Relationship of age to body weight, scrotal circumference, testicular ultrasonograms, and semen quality in Sahiwal bulls - Ejaz Ahmad; Nasim Ahmad; Zahid Naseer; Muhammad Aleem; Muhammad Sarwar Khan; Muhammad Ashiq; Muhammad Younis (Tropical Animal Health and Production, 2011)